Aplikasi Smart Inventory System Menggunakan Framework CodeIgniter di Toko Sumber Barokah Kraksaan - Andi Wijaya (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2023)
Sumber Barokah Kraksaan store sells various types of staples as well as other household needs. However, currently Sumber Barokah Stores do not yet use a computerized system so that managing stock and sales data takes a long time, as well as financial reports that are sometimes felt to be inaccurate to store owners because they still use conventional methods, namely recording in books. Shop owners often make mistakes in recording goods that have been sold, resulting in errors when ordering the next item, which results in excess stock and costs of procuring the wrong goods, causing losses for the shop owner. Monitoring goods data automatically using the ROP and ROQ methods. The research method used is the Research and Development method and the system development model uses the Prototype method. The resulting application can make it easier for store owners to monitor goods and inventory, and also make it easier to find out the results of income reporting analysis at Sumber Barokah stores, as well as make it easier for shop owners to transact with customers.